Analysis of the Characteristics of the Hydro-climatic Budget in Khanaqeen District - Ismaeel AL-Samaray, Munther Kamel (Journal of Tikrit University for Humanities, 2024)
This research aims to analyze the elements of the climatic water budget, and to show whether it is in a state of impotence or a surplus in the Khanaqin district to build information database that serves multiple aspects of life. After the analysis of the climatic elements used in the water budget, to extract the values ​​of sacrifice and compare the amount of rainfall in it to explain the state of the budget (surplus, deficit). The annual water deficit reached 2700.6 mm, and this amount exceeds the quantity between rain and evaporation/transpiration, which is 2575.16 mm. It is the amount of water equipped from the water resources for soil and plants, such as surface and groundwater to meet the needs of agricultural soil. The urgent need for irrigation has also emerged, and without that it leads to dehydration, or the lack of success of demo cultivation.